Child-player and mother-spectator: mother–child interactions and maternal scaffolding during computer games - Alon Tirosh, Michal; Ben Chitrit, David (Frontiers in Communication, 2025)
Parent–child interactions during joint play usually involve parental scaffolding, with the more skilled parent playing a more competent role by supporting the child’s learning and goal achievements. Parental scaffolding can promote children’s learning skills and contribute to their development in many areas. However, in the unique context of computer games, children are frequently more skilled or feel more skilled than their parents. This situation raises the question of whether a parent–child joint computer game interaction can still be viewed in terms of parental scaffolding of any type; and if not, to understand the nature of the parent–child interaction in the context of this medium. Observations of 20 dyads of mothers and elementary school-aged children playing computer games yielded a three phase model describing the interaction: (1) initial interaction, wherein they assume the roles of the child-player and mother-spectator; (2) struggles between mother and child; and (3) ultimate resolution through various forms of cooperation and participation. The findings indicate that the nature of the medium and mothers’ feelings of having lower skill and competence than their children often prevented them from scaffolding the specific task (the computer game played). This study demonstrates the conditions required for maternal scaffolding and expands our understanding of this developmental process in the context of computer games.